Nanocrystalline Ag3PO4 for sunlight- and ambient air-driven oxidation of amines: high photocatalytic efficiency and a facile catalyst regeneration strategy - Garg, Reeya; Mondal, Sanjit; Sahoo, Lipipuspa; Vinod, C. P.; Gautam, Ujjal K. (ACS Applied Materials & Interfaces, 2020)
Selective oxidation of amines to imines using sunlight as clean and renewable energy source is an important but challenging chemical transformation because of high reactivity of the generated imines and lack of visible light-responsive materials with high conversion rates. In addition, oxygen gas has to be purged in the reaction mixture in order to increase the reaction efficiency which, in itself, is an energy-consuming process. Herein, we report, for the first time, the use of Ag3PO4 as an excellent photocatalyst for the oxidative coupling of benzyl amines induced by ambient air in the absence of any external source of molecular oxygen at room temperature. The conversion efficiency for the selective oxidation of benzyl amine was found to be greater than 95% with a selectivity of >99% after 40 min of light irradiation indicating an exceptionally high conversion efficiency with a rate constant of 0.002 min(-1), a turnover frequency of 57 h(-1), and a quantum yield of 19%, considering all of the absorbed photons. Ag3PO4, however, is known for its poor photostability owing to a positive conduction band position and a favorable reduction potential to metallic silver. Therefore, we further employed a simple catalyst regeneration strategy and showed that the catalyst can be recycled with negligible loss of activity and selectivity.
Keywords: amine oxidation; energy harvesting; nanocrystalline Ag3PO4; Photocatalysis; regeneration strategy

Wavelength dependent luminescence decay kinetics in `quantum-confined' g-C(3)N(4)nanosheets exhibiting high photocatalytic efficiency upon plasmonic coupling - Mondal, Sanjit; Sahoo, Lipipuspa; Vaishnav, Yuvraj; Mishra, Samita; Roy, Raj Sekhar; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Journal of Materials Chemistry A, 2020)
Serendipitous observations offer newer insights into materials properties. Here we describe g-C(3)N(4)nanosheets exhibiting remarkably blue-shifted photoluminescence within the 390-580 nm range centred at 425 nm which matches more closely with its `quantum-dots', and yet is excitation-wavelength independent. Moreover, surprisingly, the luminescence decay becomes increasingly slow at higher emission wavelengths, by up to 10 times. The nanosheets absorb only a fraction of visible-light. To improve this, when we designed a nanocomposite of g-C(3)N(4)and Au nanoparticles (NPs), it retained the PL characteristics and also exhibited excellent light-harvesting and photocatalytic efficiency for benzylamine (BA) oxidation. The surface plasmon resonance of the Au NPs is responsible for the high visible-light response and assisting the reaction by the `hot-electron' injection mechanism, while an uncharacteristic, pronounced co-catalytic effect by them further improves the efficiency. The conversion is 98% with >99% selectivity over 1.5 h of natural sunlight and open-air, probably the highest efficiency for BA photo-oxidation reactions. Even though such a dual role by plasmonic NPs has remained unscrutinized, we argue that the charge-transfer processes for the `hot-carrier' injection and co-catalytic events are well-separated in time due to a much slower photon incident frequency on a catalyst particle, enabling both to occur simultaneously in the same particle.

Facile transfer of excited electrons in Au/SnS2 nanosheets for efficient solar-driven selective organic transformations - Mondal, Sanjit; Sahoo, Lipipuspa; Vinod, C. P.; Gautam, Ujjal K. (Applied Catalysis B-Environmental, 2021)
Solar driven aerial oxidation processes have gained importance in organic transformations leading to the development of many nanocrystalline photocatalysts. Although such nanomaterials have many potential advantages, they often underperform due to poor visible light absorption and rapid recombination of excitons. Incorporation of plasmonic nanoparticles (NPs) on the catalyst surfaces can extend their response to visible light and improve photocatalytic efficiency by the `hot-electron' injection mechanism. Nanostructures of SnS2 too absorb a part of the visible light to induce many photocatalytic reactions, though their ability to perform the selective and controlled organic transformations has not yet been observed. Herein, we demonstrate the first example of such transformation with the oxidative coupling of various benzylamine (BA) derivatives to imines under ambient conditions using SnS2 nanosheets (NSs). The reaction rate improves manifold and shows similar to 98 % conversion (>99 % selectivity) in 2 h under direct sunlight and open-air when the NSs were decorated with 1.5 wt% Au NPs on (Au/SnS2), making it one of the best catalysts for this reaction. We found that the large enhancement in activity upon Au loading is accompanied by a noticeable change in photo-induced charge accumulation behaviour in Au/SnS2 from the usual ``spike and overshoot'' one and contributed by facile transfer of excited electrons across the Au-SnS2 heterojunction in which Au NPs act as both sources and sinks for the photo-excited electrons. Finally, a detailed mechanism of the oxidation reaction has been proposed.
Keywords: Benzylamine oxidation; Hot-electron injection; Plasmonic nanoparticle; SnS2 nanosheet; Solar energy harvesting

Single-step insertion of M-Nx moieties in commercial carbon for sustainable bifunctional electrocatalysis: mapping insertion capacity, mass loss, and carbon reconstruction - Garg, Reeya; Sahoo, Lipipuspa; Kaur, Komalpreet; Vinod, C. P.; Gautam, Ujjal K. (Carbon, 2022)
Atomically dispersed earth-abundant metals in N-doped carbon (M-N-Cs) have emerged as a new class of electroactive materials that can match not only the performance of the precious metals but can catalyze both the cathodic and the anodic reactions due to their bifunctional behaviour. This inspires the development of simpler strategies for scale-up production since the existing ones rely on precursors whose commercial viability is not yet ascertained. Herein, we demonstrate the insertion prospects of M-Nx (M = Fe, Co, Ni) moieties, the electrocatalytic centers in the M-N-Cs, into commercial carbon to establish that a single-step heating of the inexpensive precursors is sufficient to generate bifunctional electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) with efficiencies that bypass the majority of the known catalysts. Further importantly, we quantify both the ORR and OER trends and the metal insertion limits for each metal while maintaining an atomic dispersion, without the formation of surface migration-induced clustering, because such clustering is inevitable in the existing processes to necessitate an extra acid-leaching step to remove them. We further quantify and explain for each metal a negative mass balance originating from anomalous mass loss of both metal and carbon content, and a massive reconstruction of the carbon backbone catalyzed by the very metal, an event documented for the first time though it ought to be associated with other M-N-C syntheses too. The study establishes an incredibly simple and inexpensive strategy for the realization of M-N-Cs and outlines the parameters to be considered during mass-production.
Keywords: Bifunctional catalysis; Carbon reconstruction; Commercial carbon; Metal insertion; Oxygen electrocatalysis

Ultrathin twisty PdNi alloy nanowires as highly active ORR electrocatalysts exhibiting morphology-induced durability over 200 K cycles - Sahoo, Lipipuspa; Garg, Reeya; Kaur, Komalpreet; Vinod, C. P.; Gautam, Ujjal K. (Nano Letters, 2022)
Even though the anion exchange membrane fuel cells have many advantages, the stability of their electrocatalysts for oxygen reduction reaction (ORR) has remained remarkably poor. We report here on the ultrathin twisty PdNi-alloy nanowires (NWs) exhibiting a very low reaction overpotential with an E1/2 ∼ 0.95 V versus RHE in alkaline media maintained over 200 K cycles, the highest ever recorded for an electrocatalyst. The mass activity of the used NWs is >10 times higher than fresh commercial Pt/C. Therein, Ni improves the Pd d-band center for a more efficient ORR, and its leaching continuously regenerates the surface active sites. The twisty nanowire morphology imparts multiple anchor points on the electrode surface to arrest their detachment or coalescence and extra stability from self-entanglement. The significance of the NW morphology was further confirmed from the high-temperature durability studies. The study demonstrates that tailoring the number of contact points to the electrode-surface may help realize commercial-grade stability in the highly active electrocatalysts.

Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting

Enhancing the Catalytic Activity of Pd Nanocrystals towards Suzuki Cross-Coupling by g-C3N4 Photosensitization - Mondal, Sanjit; Sahoo, Lipipuspa; Banoo, Maqsuma; Vaishnav, Yuvraj; Prabhakaran Vinod, Chathakudath; Gautam, Ujjal (Chemnanomat, 2024)
Developing renewable means of activating molecules over traditional catalysts for C-C bond formation is desirable for industrial applications. Herein, we report a strategy to improve the efficiency of Pd nanoparticles (NPs) for the Suzuki cross-coupling reactions by visible-light irradiation using g-C3N4 nanosheets (NSs) as photosensitizer. Pd NPs mounted on g-C3N4 become electron-rich under visible-light due to generation of excited electrons in g-C3N4 and thereby accelerate the rate-determining step. Remarkable photocatalytic activity was accomplished utilizing Pd/g-C3N4 for the Suzuki cross-coupling reaction in environmentally benign aqueous settings under room temperature conditions. The activity remarkably improves (similar to 2.5 times) upon light irradiation, yielding one of the highest known turnover frequencies (TOF) of 1858 h(-1) and confirming the photosensitizer role of g-C3N4. The TOF for coupling of aryl bromides is also significantly high (similar to 356 h(-1)). We establish that the low-energy/long-lived excitons preferencially transfer to Pd, paving a way for rational designing photocatalysts for various C-C coupling reactions.
Keywords: 2D graphitic carbon nitride; C-C cross-coupling; exciton transfer; heterogeneous photocatalyst; Photosensitization